Comparison Between the Efficiency of Dermatoscope and The Light Microscope for The Diagnosis of Scabies in Tripoli, 2018-2019 - Naema Shibani; Al-Dwibe, Hamida; Maha Iskandarani; Bashir Zandah (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Scabies is a common contagious skin infestation caused by a fertilized female mite Sarcoptes scabiei var. hominis and usually manifested with severe night itching and burrows that are visible to the naked eye. Early diagnosis and treatment of cases are essential, as misdiagnosis may result in outbreaks and significantly increase economic burden. The best ways to diagnose scabies in Tripoli have not been investigated yet. Thus, the study was aimed to compare the diagnostic properties and efficiency of using the dermatoscope (DS) by placing it directly on the affected skin, and a light microscope (LM) to view infested mite in the skin scrapings (SS) on diagnosing scabies. Methods. This study was conducted on 1037 patients with scabies who were randomly selected from dermatology department out of patients’ clinics of three Hospitals in Tripoli and underwent examination by using LM on skin scraping, and DS technique during the period January 2018 to June 2019. The validity of the clinical diagnosis using the two methods DS technique and LM technique provided that each one was used separately. Results. The study showed that there were no significant differences between the three hospitals in terms of diagnosing the disease by LM and DS, with a value of (p = 0.683) and (p = 0.847) respectively, however high significant differences (p value = 0.000) between the two techniques in terms of severity of infection revealed. Both techniques reached an accurate rate of 92%, that is, they are completely identical to the diagnosis of scabies, and accordingly, the infection rate (FR) of scabies with the DS technique reaches 32%, nearly similar to the LM technique by 31%. The degree of compatibility between the two devices was very high (0.832 using the Kappa scale), and it was statistically significant, with a high generalization (P-value = 0.000), meaning that the agreement between the two techniques reached 92.4%. Conclusion. The current finding suggested that the two techniques are complementary to each other.